Designing Static VAr Compensator capacity to enhance power quality in electric arc furnaces. (June 2017) - Asban, Mohammad Reza; Aghaei, Jamshid; Niknam, Taher; Akbari, Mohammad Amin
This paper introduces a method for reducing damages arising from voltage fluctuations, voltage flicker, imbalance in the three-phase and power factor reduction caused by electric arc furnaces. A novel equation is defined to calculate the susceptance values of the static var compensator control system, the active power functions of phase load as well as the reactive power ones that have been used to suppress the voltage fluctuation. By compensating the impulsive part of active power component in the impulsive loads, not only can we reduce voltage fluctuations, flicker effects, balance the system and increase the power factor, but also voltage stabilization can be directly controlled. By studying this method and simulating on Electro-Magnetic Transients Program (EMTP) software, we can see that, according to the allowable flicker limit, a compensation method can balance the system, increase power factor and resolve the problem of voltage fluctuations and flicker.